Cloud controlled watering system using blynk application/ Mohamad Amirul Farhan Abu Bakar ...[et al.] - Abu Bakar, Mohammad Amirul Farhan; Abdul Nasir, Luqman Amar; Ali, Nur Afifah; Wan Chek, Wan Ahmad Khusiairi (2018)
Gardening is an activity that people do to make their house or place become more beautiful. The most important part of gardening is watering the plants as to maintain the soil humidity. During plant watering, the excessive use of water still the main problem that still exists. This project proposed a watering system that can be controlled using internet so user can water the plants anytime and anywhere. The objectives of this research are to design a watering system consists of water pump, relay, soil moisture sensor and NodeMCU microcontroller. Next is to control the watering system using Blynk application and also to interface the NodeMCU microcontroller with Arduino Controller (IDE). Other than that, this project also uses soil moisture sensor to detect the moisture level of plants and also uses ultrasonic sensor to detect the water level of the watering tank. All of the reading of both soil moisture sensor and ultrasonic sensor will be send to the Blynk application on smartphone or PC via Internet